Utilization of Outdoor Activity to Improve Non-Science Background Students’ Understanding of Science Concepts - Kamaruddeen, Ahmed Mohammed; Nordin, Norani (American Journal of Social Sciences and Humanities, 2019)
It is necessary to expose university students to certain science or engineering related courses in Technology Management programme, irrespective of their backgrounds. Teachers and learners are frequently faced with challenges in the teaching and learning process due to insufficient exposure. Consequently, this article therefore investigates the impact of using learning object and learning activity on non-science students’ understanding of science concepts. An experiment was conducted by making use of two groups of students in Technology Management programme in a Malaysian university. The first group was not involved in any outdoor activities related to the concepts of speed, distance, and displacement while the second group was fully involved in outdoor activities related to the aforementioned concepts. The performances of both groups were compared at the end of the semesters. The descriptive statistics and analysis of variance revealed that students in the second group performed better than the students in the first group. A significant difference in the performance of the two groups was also emphasized by the analysis of variance. The findings therefore imply that the engagement of students with relevant learning objects or activities has high possibility of enhancing their understanding and facilitating knowledge transfer.